Relationship Between Anthropometric Measurements with Radiation Dose During Screening Mammography - Hameed, Doaa; Funjan, Mawada M.; Al-Sabbagh, Ahmed Abduljabar (Journal of Ecohumanism, 2024)
The incidence of breast issues, such as breast cancer, has been increasing in Iraq in recent years. Nonetheless, early detection and screening initiatives utilizing mammography and complementary ultrasoand have substantially lowered mortailty rates from this emerging disease. This study examines the relationship between breast density classification in the right and left breast, average glandular dose (AGD) for cranio-caudal (CC) and medio-lateral oblique (MLO) views, age, body mass index (BMI) across three groups of patients and compresses breast thickness. The study of population comprises of 100 paired MLO and CC mammography obtained on one mammography unit in Alawiya Educational hospital. Twenty one out of 100 females have a lesion (21%) of the total group and seventy nine out 100 females do not have a lesion ,representing 79% of total patients .Mean patient age was 46.8 years and mean body mass index (BMI) was 31.25 .Mean compreessed breast thickness was 50.35 mm for cc and 61.12 mm for MLO. Univariate analysis displayed no association between AGD in CC and MLO views with lesion in breast and BMI of patient ,negative association with age(P<0.05) ,BMI(P=0.694 for CC ,P=0.510 for MLO),lesion (P=0.209 for CC ,P=0.571 for MLO) and the relationships between average glandular dose (of both CC and MLO) and compression breast thickness (of MLO and CC) are not statistically significant (r=0.001, p= 0.996for cc and r=0.079, P=0.267 for MLO).However, there is a statisitically significant moderate positive relationship between the compression breast thickness of MLO and CC (r=-0.001, P=0.985 for cc and r=0.253** ,P=0.0001 for MLO).The AGD and dose in our routine mammography, the equivalent is within recommended limits, and the amount of radiation absorbed by glandular tissue is manageable.of breast. The study suggests a potential trend between both the average glandular dose during mammography, the breast lesions, age of patient ,compressed breast thickness and BMI, there were statistically significant between AGD , compressed breast thickness (CBT) and age . While, there were no significant differences between AGD , BMI of body patient and lesion of breast.